FTIR SPECTROSCOPIC CHARACTERIZATION OF VIRGIN COCONUT OIL PRODUCED BY FERMENTATION USING Moringa oleifera LEAVES AND BAKER’S YEAST - Loupatty, Grace; Huwae, Ana Yeti; Patty, Diana Julaidy (Prodi Fisika FST UNJA, 2026)
Virgin coconut oil (VCO) is widely recognized for its nutritional and functional properties, particularly due to the presence of bioactive compounds such as phenolic compounds that contribute to antioxidant activity. This study aims to investigate the effect of different fermentation agents, namely Moringa oleifera leaves and baker’s yeast, on the spectral characteristics and potential phenolic-related functional groups in VCO using Fourier Transform Infrared (FTIR) spectroscopy. VCO samples were produced through a fermentation extraction process using moringa leaves (VCO-K) and yeast (VCO-F). FTIR spectra in the range of 4000–400 cm⁻¹ were analyzed to identify functional groups associated with phenolic compounds and lipid structures. Both samples showed a broad O–H stretching band around 3471 cm⁻¹ (VCO-K) and 3464 cm⁻¹ (VCO-F), indicating the possible presence of hydroxyl groups related to phenolic compounds and hydrogen bonding interactions. Additional characteristic absorption bands corresponding to lipid functional groups, including C–H stretching and ester carbonyl (C=O) vibrations, were also observed. The refractive index values of VCO-K (1.454) and VCO-F (1.458) were close to reported VCO standards, indicating acceptable physicochemical quality. These findings demonstrate that FTIR spectroscopy is a useful approach for identifying molecular functional groups and investigating potential phenolic-related interactions in VCO produced using different fermentation treatments.